Investigation of therapeutic ultrasound dose on muscle phantom: an experimental study investigation of therapeutic ultrasound dose - YURDALAN, SAADET UFUK (My University, 2022)
Objective: The study aims to investigate the standardized, traceable dose amounts that will create the desired therapeutic physiological change in the tissue and prevent the risk of tissue damage in the light of metrology principles Methods: In the study carried out in TÜBİTAK National Metrology Institute Medical Metrology Laboratory, a muscle phantom simulating the acoustic properties of muscle tissue was created and thermocouples were placed in it. Ultrasound at different intensities and durations at 1 MHz frequency was applied to the phantom. The temperature changes measured by the thermocouples were recorded. Each measurement was repeated three times and averaged Results: 14 minutes application at 1 W/cm2 density, 10 minutes application at 1.5 W/cm2 density, ~7 minutes application at 2 W/cm2 density, and ~4 minutes application at 2.5 W/cm2 density have been achieved for the temperature range needed to produce therapeutic effect. Conclusions: In order to achieve the therapeutic effect, the ultrasound doses used in the procedure should be checked. Measurements in multilayer phantoms would be useful in future research.
Keywords: Tıp; Dahili Tıp Bilimleri; Tıbbi Ekoloji ve Hidroklimatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Medical Ecology and Hydroclimatology; Health Sciences; TIP, ARAŞTIRMA VE DENEYSEL; Klinik Tıp; Klinik Tıp (MED); MEDICINE, RESEARCH & EXPERIMENTAL; CLINICAL MEDICINE; Clinical Medicine (MED); Araştırma ve Teori; İncelemeler ve Referanslar (tıbbi); Research and Theory; Reviews and References (medical); Therapeutic ultrasound; muscle phantom; dose; metrology; INTRAMUSCULAR TEMPERATURE; EXERCISE; SHOULDER; Therapeutic ultrasound; muscle phantom; dose; metrology